2023
DOI: 10.1002/adpr.202200286
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Electrical Characterization of 643 nm Red InGaN Multiquantum Wells Grown on Strain‐Relaxed InGaN Templates

Abstract: Red‐emitting (≈643 nm) InGaN multiquantum well active device layers and micro‐LEDs are grown by metal organic chemical vapor deposition (MOCVD) on relaxed InGaN templates, the latter created via thermal decomposition of an InGaN underlayer, and examined via power‐ and temperature‐dependent photoluminescence and electrical measurements. Maximum internal quantum efficiencies are determined to be 7.5% at an excitation power density of 13 W cm−2, radiative recombination occurs through monomolecular recombination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…25) In 2020, 26) Pasayat et al demonstrated 0.2% on-wafer EQE for a 6 μm × 6 μm device at 10 A cm −2 emitting at 632 nm using porous GaN technology. 27) Other efforts in red InGaN microLEDs include use of a relaxed InGaN pseudosubstrates from SOITEC, 28,29) a thermal decomposition layer [30][31][32][33] and by using hybrid multiple quantum wells (MQW) stack. [34][35][36] Size independent EQE has been previously demonstrated 37) for InGaN based red microLEDs from 80 μm × 80 μm devices down to 20 μm × 20 μm devices.…”
mentioning
confidence: 99%
“…25) In 2020, 26) Pasayat et al demonstrated 0.2% on-wafer EQE for a 6 μm × 6 μm device at 10 A cm −2 emitting at 632 nm using porous GaN technology. 27) Other efforts in red InGaN microLEDs include use of a relaxed InGaN pseudosubstrates from SOITEC, 28,29) a thermal decomposition layer [30][31][32][33] and by using hybrid multiple quantum wells (MQW) stack. [34][35][36] Size independent EQE has been previously demonstrated 37) for InGaN based red microLEDs from 80 μm × 80 μm devices down to 20 μm × 20 μm devices.…”
mentioning
confidence: 99%
“…This behavior could be attributed to suppressed surface recombination and increased LEE via the sidewall. Similarly, Lim et al 67 investigated InGaN-based red lLEDs using thermal decomposition to relax the strain and found that the EQE peak of red lLEDs increased as their size decreased from 100 Â 100 to 5 Â 5 lm 2 . These results indicate that InGaN-based red lLEDs have a strong advantage in terms of overcoming the size-dependent degradation of lLEDs.…”
Section: B Size-dependent Eqe Behaviors Of Ingan-based Blue Green Red...mentioning
confidence: 97%
“…163 Another route for improving the crystal quality of InGaN-based red LEDs is relaxing the strain. In 2023, Lim et al 67 reported that the growth of an In 0.3 Ga 0.7 N decomposition layer could effectively relax the strain. This high-indium-content In 0.3 Ga 0.7 N layer was decomposed during n-InGaN/n-GaN decomposition stop-layer (DSL) growth at 950 C, which generated tensile strain in the DSL layer.…”
Section: Importance Of Growth Conditions Of Ingan Red Lledsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 45 ] Using such relaxed InGaN buffer as pseudosubstrates, high‐indium‐composition QWs for red LEDs could be grown over a full 2 inch wafer at above 800 °C, representing a promising approach for red LEDs with long wavelength and high crystal quality at the same time. [ 46 ] Even et al investigated the effect of InGaN pseudosubstrate with varying a ‐lattice parameters (3.190, 3.200, 3.205 Å) on the emission characteristics of MQWs. [ 47 ] These pseudosubstrates were found to improve the indium incorporation rate due to the reduced compositional pulling effect caused by compressive strain.…”
Section: Template For Long‐wavelength Led Growthmentioning
confidence: 99%